Transport modeling of 137Cs in soil after Fukushima Dai-Ichi Nuclear Power Plant accident by point cumulative semi-variogram method - Bilici, Sevim; Bilici, Ahmet; Kulahci, Fatih (Springer, 2019)
The positions distribution of the regional variables in space have irregular or sometimes random scatter. In such a case, their study can be rather difficult and sometimes impossible by means of differential equations. Although variogram or semi-variogram (SV) methodologyin the literature is employed to model the regional variable, in this paper, the use of the point cumulative SV (PCSV) procedure application is suggested for the Cs-137 data, which is one of the most important radioactive nuclei not only for radioactive contamination of the environment after the Fukushima Dai-Ichi Nuclear Power Plant, but any nuclear accident whatsoever. As a result of the PCSV models, the categorical description of the Cs-137 concentrations spatial distribution and transport characteristics are determined and interpreted. Prior to the application of the model, log-transformation is performed to fit the Cs-137 data to the classical normal probability distribution and the normality of data is tested by Kolmogorov-Smirnov test. According to the PCSV models, five different categories describe whole spatial distribution and transport properties of Cs-137 concentrations and also iso-radioactivity map is obtained for Cs-137.
Keywords: Fukushima; Radioactive fallout; Spatial analysis; Point cumulative semi-variogram; Cs-137 transport; Modeling